2017
DOI: 10.1371/journal.pone.0174486
|View full text |Cite
|
Sign up to set email alerts
|

Metformin inhibits gastric cancer cells metastatic traits through suppression of epithelial-mesenchymal transition in a glucose-independent manner

Abstract: Epithelial-mesenchymal transition (EMT), which is mainly recognized by upregulation of mesenchymal markers and movement of cells, is a critical stage occurred during embryo development and spreading cancerous cells. Metformin is an antidiabetic drug used in treatment of type 2 diabetes. EMT inhibitory effect of metformin has been studied in several cancers; however, it remains unknown in gastric cancer. The aim of the present study was to investigate the metformin effects on inhibition of EMT-related genes as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 39 publications
4
40
0
Order By: Relevance
“…50 and 100 μg/mL). These data agree with previous published studies, in which 7.8 mM glucose (corresponding to about 1.4 mg/mL) [66] was used as a non-fasting basal blood sugar level, while concentrations of 17.5, 25 and 33 mM glucose (corresponding to about 3.0, 4.5 and 6.0 mg/mL) to simulate hyperglycemic conditions [66][67][68]. Along with the extract, the most abundant identified phenolics, i.e.…”
Section: Pge Counteracts the Oxidative Stress Induced Under Hyperglycsupporting
confidence: 93%
“…50 and 100 μg/mL). These data agree with previous published studies, in which 7.8 mM glucose (corresponding to about 1.4 mg/mL) [66] was used as a non-fasting basal blood sugar level, while concentrations of 17.5, 25 and 33 mM glucose (corresponding to about 3.0, 4.5 and 6.0 mg/mL) to simulate hyperglycemic conditions [66][67][68]. Along with the extract, the most abundant identified phenolics, i.e.…”
Section: Pge Counteracts the Oxidative Stress Induced Under Hyperglycsupporting
confidence: 93%
“…The previous study of Chang et al, suggested that metformin can reverse EMT in GC [30]. Valaee et al and Jun et al recently confirmed this effect on the GC cell line AGS [33,34]. Indeed, the treatment of AGS cells with metformin decreased the expression of β-catenin and vimentin [33] as well as matrix metalloproteinase-9 (MMP9) and vascular endothelial growth factor (VEGF) [34].…”
Section: Metformin Inhibits Epithelial-to-mesenchymal Transitionmentioning
confidence: 88%
“…Valaee et al and Jun et al recently confirmed this effect on the GC cell line AGS [33,34]. Indeed, the treatment of AGS cells with metformin decreased the expression of β-catenin and vimentin [33] as well as matrix metalloproteinase-9 (MMP9) and vascular endothelial growth factor (VEGF) [34]. On the contrary, the expression of E-cadherin was increased in response to metformin [33,34].…”
Section: Metformin Inhibits Epithelial-to-mesenchymal Transitionmentioning
confidence: 89%
See 2 more Smart Citations